Kinesiophobia in relation to physical activity in chronic neck pain - (:unkn) unknown (IOS PRESS, 2016)
BACKGROUND: Little research is available concerning physical activity and its determinants in people with chronic neck pain. OBJECTIVE: To explore the relation between kinesiophobia and physical activity and gender effect on these relations in people with chronic neck pain. METHODS: Ninety-nine subjects (34 men and 65 women) with chronic neck pain were participated in the study. Pain intensity was assessed with Visual Analog Scale and kinesiophobia degree was determined by using Tampa Scale of Kinesiophobia. Level of physical activity was assessed with short form of the International Physical Activity Questionnaire. RESULTS: There was no statistically correlation between neck pain intensity and kinesiophobia degree (p = 0.246, r = 0.123) and physical activity level (p = 0.432, r = -0.083). It was also found that kinesiophobia degree was not correlated to physical activity level (p = 0.148, r = -0.153). There was a negative correlation between kinesiophobia degree and physical activity level only for women, not for men (p = 0.011, r = -0.318). CONCLUSIONS: Our results showed that although people with chronic neck pain reported higher pain intensity and fear of movement, pain intensity and kinesiophobia degree did not associate to their physical activity levels. It can be speculated that high kinesiophobia degrees cause low physical activity levels for women, but not for men.
Keywords: Kinesiophobia; physical activity; chronic neck pain; gender; LOW-BACK-PAIN; CHRONIC MUSCULOSKELETAL PAIN; FEAR-AVOIDANCE; RISK-FACTORS; GENERAL-POPULATION; PREVALENCE; DISABILITY; CONSEQUENCES; SCALE; QUESTIONNAIRE